A real-world study on the changing characteristics of measles antibodies in premature infants in China - Mingyan Li; Weiwei Zhang; Shuangshuang Zheng; Junxia Guo; Hanqing He; Yongjun Ma; Yan Huang; Yan Feng; Chai Ji (Taylor & Francis Group, 2024)
ABSTRACTThe waning of maternal antibodies may cause infants to lose protection against measles before receiving measles-containing vaccine (MCV). The aim of this study is to investigate the changing characteristics and influencing factors of measles antibodies in preterm infants (PT), and to provide scientific basis for optimizing MCV vaccination strategy of the target population. Blood samples were collected from PT and full-term infants (FT) at the chronological age (CA) of 3, 6, and 12 months. Measles antibodies were quantitatively detected by enzyme-linked immunosorbent assay. Demographic and vaccination information were both collected. Kruskal-Wallis rank sum test was used to compare the measles antibodies among different gestation age (GA) groups, and multiple linear regression was performed to identify the correlative factors for the antibodies. Measles antibodies of PT decreased significantly with age increasing before MCV vaccination. The positive rates of antibodies of PT were 10.80% and 3.30% at the age of 3 and 6 months, respectively (p < .001). At 12 months, the measles antibodies and seropositive rate in the infants who received MCV vaccination increased sharply (p < .001). Regression analyzes showed that the younger the GA or the older the age, the lower the antibodies at 3 months(p < .001，p = .018); while the lower measles antibody levels at 3 months and older age predicted the lower antibodies at 6 months(p < .001, p = .029). PT were susceptible to measles due to the low level of maternally derived antibodies before MCV vaccination. More efforts should be considered to protect the vulnerable population during their early postnatal life.